A CASE REPORT OF SUCCESSFUL STEROID TREATMENT IN INFANT WITH EXTRAHEPATIC CHOLESTASIS - Bagus Setyoboedi; Rendi Aji Prihaningtyas; Agrasenfani Hadi; Muhammad Nur Alpi Apriansyah; Sjamsul Arief (Faculty of Vocational Studies, Universitas Airlangga, 2025)
Background: Cholestatic jaundice in infants is a significant healthcare challenge, particularly in regions where access to surgical intervention and liver transplantation is limited. An immunologic mechanism underlies the pathogenesis of biliary atresia leading to fibro-obliteration of the bile ducts. However, the successful management of biliary atresia is often difficult because treatment typically occurs at an advanced stage. Therefore, alternative therapies that can suppress bile duct inflammation are urgently needed. Administering anti-inflammatory drugs such as methylprednisolone to infants in the early stages of cholestasis may provide opportunities to improve outcomes in the limited capacity to perform Kasai surgery and liver transplantation. Purpose: This case report describes the clinical improvement of extrahepatic cholestasis following steroid administration. Case analysis: We report a case of a 24-day-old male infant presenting with clinical symptoms of jaundice and pale stool. Liver biopsy revealed features consistent with extrahepatic obstructive cholestasis characteristic of biliary atresia. The patient was treated with methylprednisolone (a corticosteroid) and ursodeoxycholic acid without surgical intervention. Result: The combination of methylprednisolone and ursodeoxycholic acid normalized liver function tests and led to significant clinical improvement. Both jaundice and pale stools completely resolved within two months of treatment. Conclusion: Steroid therapy may provide clinical benefits for infants with extrahepatic cholestasis, particularly in settings with limited healthcare resources. Steroid administration may play a role in the suppression of the inflammatory process that causes fibrosis and bile duct obliteration in the early stages of the disease.